Analisis Reaktivasi Perundingan Indonesia–Korea Comprehensive Economic Partnership Agreement (IK-CEPA) pada Tahun 2019 - Fahra Williams, Thessalonica; Daniah, Rahmah (Department of International Relations, Universitas Mulawarman, 2023)
The economic relations that Indonesia and South Korea have established become a strong reason why both countries agreed to take their cooperation into the next level. Thus, Indonesia and South Korea agreed to enhance their economic relations through an intensified agreement: IK-CEPA, or, Indonesia-Korea Comprehensive Economic Partnership Agreement. However, ever since the first rounds of negotiation started in 2012, both countries have yet to reach a consensus on the establishment of the agreement. Thus making the negotiation processes halted. The factors that influence the termination of this agreement are mainly caused by the difference of stake & interest. It is then after 4 years, in 2019, the reactivation of this agreement is agreed upon. Both countries continued the negotiation rounds and signed the agreement in 2020. This research aims to find out why both countries decided to reactivate the negotiation process using the theory of Two Level Games by Robert Putnam. Based on the analysis, it is then found that both countries have overlapping interests in this agreement that are mutually beneficial. Using the win-set concept, the overlapping interest was found through the Two Levels: International and Domestic Level in Korea and Indonesia. This research analyzed the overlapping interest in Level II: Preferences and Coalitions & Political Institution, and Level I: Negotiation Strategy.